Evaluasi Program Posyandu Tematik Stunting (POSTIK) dalam Upaya Pencapaian Zero Stunting di Desa - Prianto, Agus; Rahmah, Lutfita (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Stunting is a serious public health problem in Indonesia, including Gununggangsir Village, Pasuruan Regency. Stunting can affect children's physical and cognitive development, and potentially reduce future productivity. To overcome this problem, the Pasuruan Regency Government launched the Stunting Thematic Posyandu Program (POSTIK), designed to reduce stunting prevalence through interventions focused on education, health checkups, and additional food delivery. However, the implementation of this program faces various challenges, such as low community participation and a lack of understanding of the importance of nutrition, which affects the effectiveness of the program in achieving zero stunting targets. Research results show that the implementation of the POSTIK Program in Gununggangsir Village has contributed significantly to the decline in stunting prevalence, seen from a decrease in stunting rates from 14.08% to 1.96% over a given period. This success is supported by the right approach, responsiveness to people's needs, and strong collaboration between the government, the private sector, and the local community. However, this study also identified several obstacles, including a lack of innovation in socialization and education activities, as well as limited access to nutritional health information. These factors hinder the public's increased awareness and understanding of the importance of stunting prevention. In conclusion, although the POSTIK Program has shown success in lowering stunting rates in Gununggangsir Village, it needs to be improved to achieve more optimal results. This study recommends improving socialization and education strategies to the community, strengthening collaboration between stakeholders, and increasing the capacity of Posyandu cadres to support the implementation of the program more effectively. This effort is expected to strengthen public understanding of the importance of nutrition, increase participation in posyandu activities, and support the achievement of zero stunting targets in the future.